2003
DOI: 10.1021/ic020639z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Low-Energy Electronic Excited States of Benzoyl-Substituted Ferrocenes

Abstract: Resonance Raman spectroscopy has been employed to probe the excited-state distortions associated with the low-energy electronic transition of benzoylferrocene and 1,1'-dibenzoylferrocene. Resonance intensity enhancement of in-plane ligand modes, in general, and the carbonyl stretching mode, in particular, supports the proposal that the excited state populated by this transition contains appreciable metal-to-ligand charge transfer character. The redistribution of charge that occurs upon populating this state we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Based on their work, Kutal and co-workers have also proposed that excitation near the MLCT energy was believed to weaken the Fe-Cp bond by reducing the hapticity of one of the Cp rings from g 5 to g 4 (Fig. 2) [29][30][31]. This was also accompanied by an increase in the electrophility of the Fe centre and thus facilitated coordination by an incoming ligand such as a weakly donating solvent (L).…”
Section: Photoinduced Reactions and Photocontrolled Polymerizations Omentioning
confidence: 99%
See 2 more Smart Citations
“…Based on their work, Kutal and co-workers have also proposed that excitation near the MLCT energy was believed to weaken the Fe-Cp bond by reducing the hapticity of one of the Cp rings from g 5 to g 4 (Fig. 2) [29][30][31]. This was also accompanied by an increase in the electrophility of the Fe centre and thus facilitated coordination by an incoming ligand such as a weakly donating solvent (L).…”
Section: Photoinduced Reactions and Photocontrolled Polymerizations Omentioning
confidence: 99%
“…In 1998, Kutal and coworkers demonstrated that 1,1 0 -dibenzoylferrocene can effectively function as photoinitiator in the anionic polymerization of ethyl-a-cyanoacrylate [28]. During the investigation to identify the mechanism for this process, Kutal et al had also carried out detailed studies on the solution photochemistry of benzoyl-substituted ferrocenes by resonance Raman and UV-Vis spectroscopy as well as electrospray ionization mass spectrometry [29,30]. The analysis led to the following major conclusions.…”
Section: Photoinduced Reactions and Photocontrolled Polymerizations Omentioning
confidence: 99%
See 1 more Smart Citation
“…Titanocenes and ferrocenes are numbered among the successfully implemented organometallic photoinitiators. [11][12][13][14][15][16][17][18][19][20][21][22][23] In a review article authored by Yang and Kutal,20 the mechanism of titanocene and ferrocene photoinitiation is delineated; however, in this research, the ferrocene photoinitiators, specifically involving free-radical initiation, will be explored in detail.…”
mentioning
confidence: 99%
“…21 The use of either ferrocene or 1,1 0 -dibenzoylferrocene has also been shown to initiate anionic photopolymerization in certain cases. [21][22][23] Thus, the utility of ferrocene or ferrocene-like derivatives to initiate a broad range of monomers is very apparent.…”
mentioning
confidence: 99%